2022
DOI: 10.1038/s41522-022-00282-3
|View full text |Cite|
|
Sign up to set email alerts
|

Deep insights into the gut microbial community of extreme longevity in south Chinese centenarians by ultra-deep metagenomics and large-scale culturomics

Abstract: The gut microbes play important roles in human longevity and the gut microbiota profile of centenarians shows some unique features from young adults. Nowadays, most microbial studies on longevity are commonly based on metagenomic sequencing which may lose information about the functional microbes with extremely low abundance. Here, we combined in-depth metagenomic sequencing and large-scale culturomics to reveal the unique gut microbial structure of a Chinese longevity population, and to explore the possible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…1B, Supplementary Fig. 3C), as observed previously (6). With respect to the bacteriome, we could observe that at phylum level, Firmicutes, Proteobacteria, Actinobacteriota, and Bacteroidota were the dominant bacterial taxa in each age group, which was in accordance with previous reports with different cohorts (Fig.…”
Section: Aging Is Mirrored In the Overall Microbiome Profilesupporting
confidence: 92%
See 1 more Smart Citation
“…1B, Supplementary Fig. 3C), as observed previously (6). With respect to the bacteriome, we could observe that at phylum level, Firmicutes, Proteobacteria, Actinobacteriota, and Bacteroidota were the dominant bacterial taxa in each age group, which was in accordance with previous reports with different cohorts (Fig.…”
Section: Aging Is Mirrored In the Overall Microbiome Profilesupporting
confidence: 92%
“…We then delved more into the differences of the archaeal profile of different age groups. The increased relative abundance of M. smithii with advancement of age, and the possible increased abundance of this methanogen prior to longevity has been previously reported (62). Our study however provided evidence that although there is a steady increase in relative abundance of Methanobacteria with the progression of age, there is a transition phase where the OAs are characterized by the increased abundance of Ca.…”
Section: Discussionsupporting
confidence: 70%
“…Consistent with previous findings, age-related significantly increased abundances of Methanobrevibacter , methanogenic genes, and microbial diversity may be associated with prolonged colonic transit time, which was observed in older adults 47 , 48 . Methanobrevibacter is gradually enriched with age, which may have a role in longevity 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome of centenarians, as models of longevity and successful ageing, has been particularly studied. It is characterized by depletion of taxa with purported health-promoting activity, including synthesis of short-chain fatty acids (SCFAs), fundamental anti-inflammatory and pro-anabolic mediators [5][6][7][8]. However, one study conducted in Chinese centenarians and their offspring suggested that metabolic capacity of synthetizing SCFAs was maintained, at the functional level, in extreme ages [8].…”
Section: Healthy Ageingmentioning
confidence: 99%
“…However, one study conducted in Chinese centenarians and their offspring suggested that metabolic capacity of synthetizing SCFAs was maintained, at the functional level, in extreme ages [8]. The microbiome of centenarians was also characterized by high biodiversity, increased representation of Prevotella at the expense of Bacteroides, and high abundance of 'core taxa' such as Bifidobacteria and Methanobrevibacter in comparison with younger people [5][6][7][8].…”
Section: Healthy Ageingmentioning
confidence: 99%